2012
DOI: 10.1104/pp.112.205500
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome-Mediated Turnover of Arabidopsis MED25 Is Coupled to the Activation of FLOWERING LOCUS T Transcription  

Abstract: The Mediator complex is a greater than 1-megadalton complex, composed of about 30 subunits and found in most eukaryotes, whose main role is to transmit signals from DNA-bound transcription factors to RNA Polymerase II. The proteasome is emerging as an important regulator of transcription during both initiation and elongation. It is increasing the number of cases where the proteolysis of transcriptional activators by the proteasome activates their function. This counterintuitive phenomenon was called “activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 59 publications
3
41
0
Order By: Relevance
“…MED25 interacts directly with the transcriptional activation domain of VP16 (Vojnic et al, 2011). The ortholog of MED25 in Arabidopsis, known as PFT1 (Phytochrome and Flowering Time1) (Cerdán and Chory, 2003;Bäckström et al, 2007), was identified as a factor involved in phy signaling and flowering time (Cerdán and Chory, 2003;Iñigo et al, 2012aIñigo et al, , 2012bKlose et al, 2012). Our future investigation will test the hypothesis that HMR's 9aaTAD interacts directly with PFT1 to promote gene activation.…”
Section: Hmr Is a Transcriptional Coactivator Required For The Expresmentioning
confidence: 99%
“…MED25 interacts directly with the transcriptional activation domain of VP16 (Vojnic et al, 2011). The ortholog of MED25 in Arabidopsis, known as PFT1 (Phytochrome and Flowering Time1) (Cerdán and Chory, 2003;Bäckström et al, 2007), was identified as a factor involved in phy signaling and flowering time (Cerdán and Chory, 2003;Iñigo et al, 2012aIñigo et al, , 2012bKlose et al, 2012). Our future investigation will test the hypothesis that HMR's 9aaTAD interacts directly with PFT1 to promote gene activation.…”
Section: Hmr Is a Transcriptional Coactivator Required For The Expresmentioning
confidence: 99%
“…Red light and blue light play antagonistic roles in the regulation of CO mRNA transcription. In response to red light, phyB down-regulates CO mRNA transcription through factors such as PHYTOCHROME AND FLOWERING TIME 1 (8)(9)(10). In contrast, cry2 and phyA up-regulate CO mRNA transcription (7,11).…”
mentioning
confidence: 99%
“…Genetic evidence suggests that PFT1 serves an activating role both in CO transcription as well as FT transcription, through independent mechanisms (Inigo et al, 2012b). At least at FT, PFT1 is degraded by the proteasome through the action of two interacting proteins MED25-BINDING RING-H2 PROTEIN1 (MBR1: At2g15530) and MRB2 (At4g34040) (Inigo et al, 2012a). Degradation of PFT1 is important for activation of FT, as inhibition of PFT1 degradation prevents FT activation.…”
Section: Ft Chromatin Structurementioning
confidence: 99%